Developing Arabic speaking skills through Kitab Akhlaq Lil Baniin: A case study on Islamic Boarding School Darul Ihsan Hamparan Perak - Husna, Maulidatul; Rozi, Fahrur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to determine the effectiveness of Arabic language learning using the Akhlak Lil Baniin book for class IX A students at the Darul Ihsan Modern Islamic Boarding School. The study was conducted with a qualitative approach and descriptive analysis, through observation, interviews, and documentation. The results showed that the use of this book was able to improve the Maharah Kalam (speaking ability) and self-confidence of students. Teaching is also supported by various learning methods and media so as not to be boring. The Akhlak Lil Baniin Book Volume 1 contains 33 titles in 56 pages that discuss noble morals, with easy-to-understand Arabic. Evaluation was carried out to improve the quality of learning. This study contributes to the development of Arabic language learning methods in Islamic boarding schools, especially in improving the Maharah Kalam (speaking ability) of students. By using the Akhlak Lil Baniin book as a teaching material, this study shows that material based on moral values can be an effective means of learning Arabic. In addition, this study also provides input for Arabic teachers to integrate various learning methods and media to increase student participation and confidence in speaking Arabic. It is hoped that these findings can be used as a reference in developing the curriculum and strategies for teaching Arabic in Islamic boarding schools or other Islamic educational institutionsز